Prasugrel compared to ticagrelor in primary PCI. (25th November 2020) - Doerler, J; Edlinger, M; Alber, H; Berger, R; Frick, M; Hammerer, M; Hasun, M; Huber, K; Lamm, G; Lassnig, E; Von Lewinski, D; Roithinger, F.X; et al.
Abstract: Background: Prasugrel and ticagrelor have similar recommendations in the setting of primary PCI by current guidelines. Data comparing both in daily clinical practice of primary PCI for ST-elevation myocardial infarction is limited. Purpose: To compare the effect of prasugrel and ticagrelor on in-hospital outcomes after primary PCI. Methods and results: We prospectively enrolled 5365 patients treated with prasugrel (n=2785, 51.9%) or ticagrelor (n=2580; 48.1%) in the setting of primary PCI from January 2011 to December 2018 in a nationwide registry. In-hospital outcomes were compared and multiple logistic regression analysis was performed. Prasugrel treated patients were younger, less often in cardiogenic shock, with lower rates of previous stroke and had shorter ischemic time. Both groups showed similar rates of previous MI, diabetes and current resuscitation. In the univariate analysis mortality was lower in patients with prasugrel (2.5% vs. 4.4% p<0.01). Similarly, MACE (3.3% vs. 5.3%, p<0.01) and NACE (4.0% vs. 5.7% p<0.01) were lower in prasugrel treated patients, whereas major bleeding events did not differ (0.4% vs. 0.6% p=0.24). After adjustment in multivariable analysis mortality (0.99 95% CI 0.57 to 1.72), MACE (OR 0.99 95% CI 0.65 to 1.52) as well as NACE (0.86 95% CI 0.61 to 1.22) did not differ in patients treated with prasugrel compared to ticagrelor. Conclusion: Patients treated with prasugrel showed improved outcomes compared to ticagrelor in a large cohort of primary PCI. However, after adjustment for confounders the Advantage of prasugrel in primary PCI did not persist. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Austrian Society of Cardiology